Antibiotics administered within 1 hour to adult emergency department patients screened positive for sepsis: a systematic review. (August 2020) - Xantus, Gabor; Allen, Penny; Norman, Sharon; Kanizsai, Peter
Abstract : Objective: The 2018 Surviving Sepsis Campaign update recommended instigating the Sepsis-6 bundle within 1 h; however, the supporting evidence is weak. The objective was to systematically review the literature to determine whether there is mortality benefit (hospital or 28/30-day survival) associated with administration of antibiotics <1 h to adult emergency department (ED) patients screened positive for sepsis using systemic inflammatory response system criteria. Methods: A systematic review and meta-analysis were conducted. Embase, CINAHL, Medline, Pubmed, Cochrane Library and grey literature were searched for articles published between 2012 and 2019. Results: From 232 identified articles, seven met the inclusion criteria. Due to the small number of articles that fit the inclusion criteria and the considerable heterogeneity ( I 2 = 92.6%, P < 0.001), only the results of the systematic review are reported. Three of the seven studies demonstrated survival benefit for patients who screened positive for sepsis who were administered antibiotics ⩽1 h after presentation to the ED. Four studies reported no statistically significant improvement in survival associated with administration of antibiotics within 1 h of ED presentation. Interestingly, two studies reported worse outcomes associated with early administration of antibiotics in patients with low acuity sepsis. Conclusion: There is equivocal evidence of in-hospital or 28/30-day survival benefit associated with antibiotics administered ⩽1 h after presentation to the ED for patients who screened positive for sepsis. Further research is needed to identify the exact patient group, which would truly benefit from initiation of antibiotics <1 h after ED presentation. Abstract : Supplemental Digital Content is available in the text.